Apakah Kepribadian Menentukan Pemilihan Media Komunikasi? Metaanalisis Terhadap Hubungan Kepribadian Extraversion, Neuroticism, dan Openness to Experience dengan Penggunaan Email - Nelia Ramdhani (Faculty of Psychology, Universitas Gadjah Mada, 2007)
As communication technologies such as e-mail have becoming indispensable for business communication, the study of the use and effects of technologies is increasingly relevant. This study is aimed at analyzing the correlation between personality traits and the choice of communication media. Research data from 22 studies published in the journals and the articles posted in the internet in the years of 1999 – 2006 were analyzed using meta analysis technique. The total of 4267 participants were involved in the research. Analysis was focused only on the correlation between three personality traits: extraversion, neuroticism, openness to experience, and the use of email. Two statis¬tical technique error corrections were applied in analyzing the data, namely sampling error correction and measurement error correction. It was found that after sampling error correction was calculated the correlation between extraversion and email usage was (ř) = 0,33. Further, when measurement error was also calculated, the correlation between those two variables increased to (ρ) = 0,38. When sampling error corection was applied, the correlation between neuroticism and email usage was (ř) = 0,13. Similar to extra¬version when measurement error was cor¬rect¬ed, the correlation between these two variables increased to (ρ) = 0,14. The corre¬la¬tion between openness to experience with email usage was (ř) = 0,30 when sampling error correction was calculated. Further when the measurement error correction was applied the coeficient correlation was increas¬ed to (ρ) = 0,33. These findings indi¬cated that personality traits correlate with email usage. Keywords: meta analisis, extraversion, neu¬ro-ticism, openness to experience, email